ANALISIS EKONOMI TERHADAP STRUKTUR, PERILAKU, DAN KINERJA PASAR PUPUK DI JAWA TIMUR (Kasus di Kabupaten Lumajang dan Kabupaten Ngawi) - M Umar Burhan; Agus Suman; M Pudjiharjo; Noer Soetjipto (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2011)
The objectives of this research are: (1) to analyze the market structure of subsidizedfertilizer in East Java, (2) to analyze the need of subsidized fertilizer which should beallocated to their farms, (3) to observe the deviation, if any, of subsidized fertilizerdistribution along the distribution channel.This research found that the market struc-ture has the following characteristics: the access of market information is generallyquite even among distributors at the same level but not between different level. Fromthe market conduct point of view, it is found that there are rent seeking behaviorsresulting in some deviation in distribution channel as mentioned above. It is the resultof market structure being characterized by oligopolistic in nature. Such market struc-ture and conducts result Â in the level of fertilizer prices far above the highest retailprice set by the government, but farmers are forced to buy because they are in emer-gency need.Keywords : Fertilizer, rent-seeking, oligopoly, scarcity